EFEKTIVITAS MODEL PROBLEM SOLVING BERBANTUAN SELF-DIAGNOSIS SHEET DALAM MEREMEDIASI KESALAHAN MENYELESAIKAN SOAL MATERI ENERGI - Oktavianus Liyu; Haratua Tiur Maria S; Erwina Oktavianty (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2020)
The purpose of this study was to examine the effectiveness of Problem Solving Model assisted with the self-diagnosis sheet to remediating students' mistake in solving about energy on grade of SMAN 5 Pontianak. The form of research was pre-experimental design with one group pre-test post-test design. The data collection was used in this research was essay tests of five questions. The research sample was chosen using the Intact Group technique. In generaly the percentage of students’ mistakes completing questions before remediation is 54.32%, while the percentage of students' mistakes completing questions after remediation is 13.81%. The used of self-diagnosis sheet assisted problem solving models was effective in remediating students' mistakes in solving problems with the effect size of 0.75 categorized as high. This research is expected to be used as an alternative learning activity in class to overcome the mistakes in completing questions experienced by students.